2002
DOI: 10.1016/s0169-4332(01)00646-8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the absorption length of CO2, Nd:YAG and high power diode laser radiation for a selected grouting material

Abstract: The laser beam absorption lengths of CO 2 , Nd:YAG and a high power diode laser (HPDL) radiation for a newly developed SiO 2 /Al 2 O 3 -based tile grout have been determined through the application of Beer-Lambert's law. The findings revealed marked differences in the absorption lengths despite the material having similar beam absorption coefficients for the lasers. The absorption lengths for the SiO 2 /Al 2 O 3 -based tile grout for CO 2 , Nd:YAG and HPDL radiation were calculated as being 232±11 µm, 193±4 µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…ffiffiffiffiffiffi ffi a s t p [38] Usually, if the corresponding physical properties of the target and technique parameters are given, one can directly solve the heat conduction equation by analytical or numerical methods to obtain accurate results of target temperature at different times and positions, and the evolution of the dynamic interface. This research method for LPLA is quite universal.…”
Section: Main Theoretical Results Of the Thermodynamics Of Long-pulsementioning
confidence: 99%
See 1 more Smart Citation
“…ffiffiffiffiffiffi ffi a s t p [38] Usually, if the corresponding physical properties of the target and technique parameters are given, one can directly solve the heat conduction equation by analytical or numerical methods to obtain accurate results of target temperature at different times and positions, and the evolution of the dynamic interface. This research method for LPLA is quite universal.…”
Section: Main Theoretical Results Of the Thermodynamics Of Long-pulsementioning
confidence: 99%
“…For most ceramic materials with a low reflectivity for infrared lasers, CO 2 laser is a good candidate for ceramic drilling (37,38). Lawrence et al confirmed that for CO 2 laser, the absorption length for Al 2 O 3 /SiO 2 -based refractory material is three orders of magnitude greater than most of metals (38,40). Unlike most metals, the polymer materials under laser irradiation can produce a deeper thermal penetration.…”
Section: Laser Drilling and Cuttingmentioning
confidence: 99%
“…An example would be Beer-Lambert penetration of photons due to material-laser combination (i.e. CO 2 of 10.6um wavelength vs. SiO 2 /Al 2 O 3 material [20]) or due to scattering in powder [21].…”
Section: Theoretical Definitions Facilitating Dt-driven Process Controlmentioning
confidence: 99%
“…Coating removal mechanism begins after the absorption of laser intensity to the coating layers has exceeded the ablation threshold of the coated material (Metsios, Dai, Chard, McComb, & Kwon, 2018;Poprawe, 2011;Targowski et al, 2009). This can be described by the Beer -Lambert absorption law, as given in Equation ( 9) (Kumar et al, 2012;Lawrence, Minami, Li, Edwards, & Gale, 2002;Schmidt et al, 2003).…”
Section: Heat Affected Zonementioning
confidence: 99%